The Preparation of Nano Composites and Their Applications in Solar Energy Conversion - Yang, Nailiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book mainly focuses on the solar energy conversion with the nanomaterials. It describes the applications on two dimensional carbon nanomaterials: graphene and graphdiyne. Also, works on conductive polymer and bio-inspired material is included. The work described here is the first few reports on the applications of graphene, which becomes one of the hottest materials nowadays. This work also proves and studies the charge transfer between the semi-conductor and graphene interface, which is benefit to the applications in solar cells and photocatalysis. At the same time, method to synthesize and assemble the given nanomaterials (TiO2 nanosheets, gold nanoparticles, graphene, PS-PAA, PANI) is detailed, which is easier to the readers to repeat the experiments.
Introduction -- Two-Dimensional Graphene Bridges to Enhance Photoinduced Charge Transport in Dye-Sensitized Solar Cells -- Granum-Like Stacking Structures for Improving Photo-electric Conversion -- Enhanced Light Harvesting in Plasmonic Dye-Sensitized Solar Cells by Using Plasmonic Effect -- Photocatalytic Properties of Graphdiyne and Graphene Modified TiO2: From Theory to Experiment -- Conclusion and Outlook.
Keywords: Inorganic chemistry; Renewable energy sources; Nanotechnology; Chemistry, Technical; Inorganic Chemistry; Renewable Energy; Nanotechnology; Industrial Chemistry